Platinum and Cerium-Zirconium Oxide Co-Doped Membrane for Mitigated H2 Crossover and Ionomer Degradation in PEWE. Issue 10 (1st October 2022) - Zhang, Zheyu; Han, Zongyi; Testino, Andrea; Gubler, Lorenz
Abstract : The use of thinner membranes in polymer electrolyte water electrolysis increases the likelihood of forming an explosive H2 /O2 mixture in the anode stream. Doping Pt nanoparticles into a Nafion membrane as recombination catalyst effectively lowers the hydrogen crossover. Here, we propose the additional co-doping of cerium-zirconium oxide as radical scavenger to mitigate membrane degradation. Our results show over 4-fold reduction of anodic hydrogen content compared to a non-doped membrane, and a nearly 3-fold decrease of fluoride release rate compared to the membrane with only Pt-doping at 80 °C and differential pressure ( p c = 3 bar, p a = 1 bar) operation.